On conjugate product of complex polynomials - Wu, A.; Duan, G.; Feng, G.; Liu, Wan-Quan (Elsevier, 2011)
Some concepts, such as divisibility, coprimeness, in the framework of ordinary polynomial product are extended to the framework of conjugate product. Euclidean algorithm for obtaining greatest common divisors in the framework of conjugate product is also established. Some criteria for coprimeness are established.